Comparison of Aloe Vera versus Petroleum Jelly in Reduction of Diaper Dermatitis among Infants admitted in BPKIHS (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Diaper dermatitis is one of the most common inflammatory skin reactions during infancy caused by high humidity, maceration and friction due to contact with urine and faeces. Application of a suitable barrier preparation can easily treat diaper dermatitis. This study aims to compare effectiveness of Aloe Vera and Petroleum Jelly in reduction of diaper dermatitis among infants admitted in BPKIHS.MATERIALS AND METHODS: A quasi- experimental study design was adopted. Fifty infants meeting eligible criteria were selected by consecutive sampling technique. Data was collected using semi structured interview questionnaire and observation Proforma for skin grading. Descriptive and inferential statistic (Chi square test) was used to analyse the data.RESULTS: The severity of diaper dermatitis was reduced in both groups although the reduction rate was not statistically significant. After application of aloevera jelly the mean intensity of Diaper Dermatitis was reduced from 2.04 to 1.4 and after application of petroleum jelly it was reduced from 2.21 to 1.2. Frequency of diaper change has significant association with development of Diaper Dermatitis (p=0.04).CONCLUSIONS:The study concludes petroleum jelly to be more effective than Aloe Vera Jelly for reduction of infantile diaper dermatitis.